Keanekaragaman Flora Mangrove pada Tingkat Pohon di Cagar Alam Pulau Dua Banten - Novi Ramadani Pratiwi; Futihatun Nur Amalia; Indah Fitri Rahmawati; Setyoko Setyoko (Fakultas MIPA UNM, 2022)
Abstract. One of the countries that has the largest mangrove forest is Indonesia, the area of mangrove forests in Indonesia reaches 3.1 million ha. Mangroves can live in tropical and subtropical climates, mangroves have so many benefits, one of which is to prevent disasters such as tsunamis and protect beaches from erosion. This research was conducted in the Pulau Dua Nature Reserve in the Banten area. This study uses a linear quadratic transect method by determining the location of the study as many as 2 station points. Data analysis was carried out quantitatively using vegetation analysis. Based on the results of the research conducted, it shows that the value of the mangrove flora diversity index is classified as low, namely H'<1. The species of mangrove flora were found such as Avicennia germinans, Avicennia marina, Avicennia officinalis, Bruguiera parviflora, and Rhizophora apiculata. The condition of the mangrove forest in the Pulau Dua Banten Nature Reserve is still relatively natural, because it is still very well preserved and the diversity of flora and fauna is still high.Keywords: mangrove, nature reserve, dua banten island